Yield Response and Physiological Adaptation of Green Bean to Photovoltaic Greenhouses - Cossu, Marco; Sirigu, Antonella; Deligios, Paola A.; Farci, Roberta; Carboni, Gianluca; Urracci, Giulia; Ledda, Luigi (Frontiers in Plant Science, 2021)
The cultivation of the horticultural crops inside photovoltaic greenhouses (PVG) should be studied in relation to the shading cast by the photovoltaic (PV) panels on the roof. This work evaluated the green bean cultivation inside PVGs with a percentage of the greenhouse area covered with PV panels (PV cover ratio, PVR) ranging from 25 to 100%. Three dwarf green bean cycles (Phaseolus vulgaris L., cv. Valentino) were conducted inside an iron–plastic PVG with a PVR of 50%. The average yield was 31% lower than a conventional greenhouse. Adverse effects on quality were noticed under the PV roof, including a reduction of pod weight, size, and caliber. Negative net photosynthetic assimilation rates were observed on the plants under the PV roof, which adapted by relocating more resources to the stems, increasing the specific leaf area (SLA), leaf area ratio (LAR), and the radiation use efficiency (RUE). The fresh yield increased by 0.44% for each additional 1% of cumulated PAR. Based on the linear regressions between measured yield and cumulated PAR, a limited yield reduction of 16% was calculated inside a PVG with maximum PVR of 25%, whereas an average yield loss of 52% can occur with a PVR of 100%. The economic trade-off between energy and green bean yield can be achieved with a PVR of 10%. The same experimental approach can be used as a decision support tool to identify other crops suitable for cultivation inside PVGs and assess the agricultural sustainability of the mixed system.